Historisasi Kriminalitas dalam Novel Lampuki Karya Arafat Nur: Perspektif Kriminologi Sastra - Hasiliana Hasiliana; Suantoko Suantoko (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The form of historicization in literary criminology views criminality as the result of power relations, unequal social structures, and history. Criminal acts in historicization are always placed in a specific time and place context, tracing how a behavior is considered “criminal” or “against the law” depending on the historical construction formed by the legal system, the state, and the rulers. Historicization also reveals that what is referred to as crime is not absolute, but can change according to historical developments and power struggles. The purpose of this study is to describe the form of criminalization in the novel Lampuki, which is not merely an individual deviant act, but a reflection of historical trauma and a flawed social structure. The approach used is literary sociology. This study uses a descriptive-qualitative method with reading and note-taking techniques obtained from the novel Lampuki by Arafat Nur in the form of sentences and paragraphs. The results of the study show that there are seven data points that fall under the form of criminalization of history. From the seven data points, three findings were generalized and discovered in Arafat Nur novel Lampuki, namely: (1) transgenerational trauma of violence, (2) the destruction of the socio-cultural structure, and (3) dark figure of crime.